PROSES BERPIKIR SISWA BERKEBUTUHAN KHUSUS DALAM PEMECAHAN MASALAH MATEMATIKA MENGGUNAKAN ALAT PERAGA - Naufalia Nuraya; Sri Hastuti; Ardi Dwi Susandi (SIGMA, 2022)
This study aims to describe the thinking process of Attention Deficit Hyperactivity disorder (ADHD) students in solving mathematical problems using teaching aids. This research is a qualitative research that uses a descriptive research methodology. The subjects of this study were students at one of the Special Schools (SLB) in Cirebon City as many as 3 ADHD students who had received learning using visual aids. Then the subject selection technique used purposive sampling technique. The main instrument in this research is the researcher himself. Auxiliary instrument in this research is math problem in essay form. Data collection techniques using interview and test techniques. The data analysis techniques in this study consist of: (1) classifying the data, (2) presenting the data, and (3) concluding the data that has been obtained. The results showed that the thinking processes of ADHD students: (1) ADHD students can form understanding when answering questions about flat shapes; (2) ADHD students are not able to repeat the answers that have been obtained; (3) ADHD students are unable to use other strategies in solving given math problems; (4) ADHD students are not able to give reasons for the answers that have been obtained on the written answer sheet; and (5) ADHD students cannot give the correct conclusion on the answers that have been obtained.